Meflin-Positive Cancer-Associated Fibroblasts Inhibit Pancreatic Carcinogenesis - Mizutani, Yasuyuki; Kobayashi, Hiroki; Iida, Tadashi; Asai, Naoya; Masamune, Atsushi; Hara, Akitoshi; Esaki, Nobutoshi; Ushida, Kaori; Mii, Shinji; Shiraki, Yukihiro; Ando, Kenju; Weng, Liang; et al. (Cancer research (Chicago, Ill.), 2019)
Cancer-associated fibroblasts (CAF) constitute a major component of the tumor microenvironment. Recent observations in genetically engineered mouse models and clinical studies have suggested that there may exist at least two functionally different populations of CAFs, that is, cancer-promoting CAFs (pCAF) and cancer-restraining CAFs (rCAF). Although various pCAF markers have been identified, the identity of rCAFs remains unknown because of the lack of rCAF-specific marker(s). In this study, we found that Meflin, a glycosylphosphatidylinositol-anchored protein that is a marker of mesenchymal stromal/stem cells and maintains their undifferentiated state, is expressed by pancreatic stellate cells that are a source of CAFs in pancreatic ductal adenocarcinoma (PDAC). hybridization analysis of 71 human PDAC tissues revealed that the infiltration of Meflin-positive CAFs correlated with favorable patient outcome. Consistent herewith, Meflin deficiency led to significant tumor progression with poorly differentiated histology in a PDAC mouse model. Similarly, genetic ablation of Meflin-positive CAFs resulted in poor differentiation of tumors in a syngeneic transplantation model. Conversely, delivery of a Meflin-expressing lentivirus into the tumor stroma or overexpression of Meflin in CAFs suppressed the growth of xenograft tumors. Lineage tracing revealed that Meflin-positive cells gave rise to α-smooth muscle actin-positive CAFs that are positive or negative for Meflin, suggesting a mechanism for generating CAF heterogeneity. Meflin deficiency or low expression resulted in straightened stromal collagen fibers, which represent a signature for aggressive tumors, in mouse or human PDAC tissues, respectively. Together, the data suggest that Meflin is a marker of rCAFs that suppress PDAC progression. SIGNIFICANCE: Meflin marks and functionally contributes to a subset of cancer-associated fibroblasts that exert antitumoral effects. http://cancerres.aacrjournals.org/content/canres/79/20/5367/F1.large.jpg.